Laparoscopic or open liver resection for intrahepatic cholangiocarcinoma: A meta-analysis and systematic review - Zhao, Xin; Gao, Feng-wei; Jiang, Kang-yi; Yang, Jie; Xie, Qing-yun; Gong, Jie; Yang, Man-yu; Mao, Tian-yang; Lei, Ze-hua (Frontiers in Oncology, 2023)
Background: Although laparoscopic hepatectomy has been widely used in the treatment of benign and malignant liver diseases, its applicability in intrahepatic cholangiocarcinoma (ICC) is controversial. We conducted a meta-analysis to compare the short-term and long-term outcomes of laparoscopic hepatectomy (Lap-ICC) and open hepatectomy (Open-ICC) in ICC patients. Methods: The PubMed, Web of science, Cochrane Library, China National Knowledge Infrastructure and other databases were searched for the relevant literature. The research data were extracted according to the inclusion and exclusion criteria. Results: Seventeen studies, including 3975 ICC patients, were selected for the meta-analysis. Compared to Open-ICC, Lap-ICC had lower rates of lymph node dissection (OR=0.44, P=0.01) and metastasis (OR=0.58, P=0.03), along with less intraoperative bleeding (MD=-128.43 ml, P<0.01) lower blood transfusion rate (OR=0.43, P<0.01), shorter hospital stay (MD=-2.75 day, P<0.01), higher R0 resection rate (OR=1.60, P<0.01), and lower tumor recurrence rate (OR=0.67, P=0.01). However, there was no difference between the two groups in terms of operation time, number of lymph node dissection, incision margin distance, overall complications rate, severe complications rate, and the 1-, 3- and 5-year DFS and OS rates. PSM subgroup analysis further verified the reliability of the above results. Conclusion: Laparoscopic hepatectomy is partially superior to open hepatectomy in terms of less bleeding, shorter hospital stay and higher R0 resection rate, while the long-term efficacy of the two approaches is similar.